What is the role of randomised trials in implementation science? - Foy, Robbie; Ivers, Noah M.; Grimshaw, Jeremy M.; Wilson, Paul M. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background There is a consistent demand for implementation science to inform global efforts to close the gap between evidence and practice. Key evaluation questions for any given implementation strategy concern the assessment and understanding of effects. Randomised trials are generally accepted as offering the most trustworthy design for establishing effectiveness but may be underused in implementation science. Main body There is a continuing debate about the primacy of the place of randomised trials in evaluating implementation strategies, especially given the evolution of more rigorous quasi-experimental designs. Further critiques of trials for implementation science highlight that they cannot provide ‘real world’ evidence, address urgent and important questions, explain complex interventions nor understand contextual influences. We respond to these critiques of trials and highlight opportunities to enhance their timeliness and relevance through innovative designs, embedding within large-scale improvement programmes and harnessing routine data. Our suggestions for optimising the conditions for randomised trials of implementation strategies include strengthening partnerships with policy-makers and clinical leaders to realise the long-term value of rigorous evaluation and accelerating ethical approvals and decluttering governance procedures for lower risk studies. Conclusion Policy-makers and researchers should avoid prematurely discarding trial designs when evaluating implementation strategies and work to enhance the conditions for their conduct.